2020
DOI: 10.1007/s10620-020-06319-x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Gluconate Induces Potentially Cancer Chemopreventive Activity in Barrett’s Esophagus: A Phase 1 Pilot Study

Abstract: Background Chemopreventive effects of zinc for esophageal cancer have been well documented in animal models. This prospective study explores if a similar, potentially chemopreventive action can be seen in Barrett's esophagus (BE) in humans. Aims To determine if molecular evidence can be obtained potentially indicating zinc's chemopreventive action in Barrett's metaplasia. Methods Patients with a prior BE diagnosis were placed on oral zinc gluconate (14 days of 26.4 mg zinc BID) or a sodium gluconate placebo, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…EA has a positive effect on the prevention and treatment of cancer. EA can prevent and control the occurrence of cancer through four aspects: (1) Inducing apoptosis of cancer cells; EA can induce and promote the apoptosis of esophageal squamous cell carcinoma (ESCC) cells (Valenzano et al, 2021), and prostate cancer cells (Deng et al, 2017); (2) Inhibition of cancer cell growth; EA can inhibit the growth of human hepatoma cells (HepG2 cells) in G0/G1 phase (Song, Li, et al, 2016), and inhibit the proliferation of cervical cancer cells (Guo et al, 2016); (3) Inhibit the invasion of cancer cells; EA plays an important role by inhibiting the invasion of gastric cancer (GC) cells; (4) Inhibit the expression of enzymes in cancer cells; During the treatment of breast cancer, EA down‐regulates the expression of cyclin‐dependent kinase 6 (CDK6) in breast cancer cell lines (Mişe et al, 2014).…”
Section: Bioactivity Of Ellagic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…EA has a positive effect on the prevention and treatment of cancer. EA can prevent and control the occurrence of cancer through four aspects: (1) Inducing apoptosis of cancer cells; EA can induce and promote the apoptosis of esophageal squamous cell carcinoma (ESCC) cells (Valenzano et al, 2021), and prostate cancer cells (Deng et al, 2017); (2) Inhibition of cancer cell growth; EA can inhibit the growth of human hepatoma cells (HepG2 cells) in G0/G1 phase (Song, Li, et al, 2016), and inhibit the proliferation of cervical cancer cells (Guo et al, 2016); (3) Inhibit the invasion of cancer cells; EA plays an important role by inhibiting the invasion of gastric cancer (GC) cells; (4) Inhibit the expression of enzymes in cancer cells; During the treatment of breast cancer, EA down‐regulates the expression of cyclin‐dependent kinase 6 (CDK6) in breast cancer cell lines (Mişe et al, 2014).…”
Section: Bioactivity Of Ellagic Acidmentioning
confidence: 99%
“…EA has a positive effect on the prevention and treatment of cancer. EA can prevent and control the occurrence of cancer through four aspects: (1) Inducing apoptosis of cancer cells; EA can induce and promote the apoptosis of esophageal squamous cell carcinoma (ESCC) cells (Valenzano et al, 2021), and prostate cancer cells (Deng et al, 2017);…”
Section: Anti-tumormentioning
confidence: 99%
“…In a pilot placebo-controlled trial of 10 BE patients, oral zinc supplementation for 2 weeks showed increased apoptosis, upregulation of tumor suppressor mRNAs, a decreased inflammatory state, and decreased epithelial-to-mesenchymal transition signaling in the cells. 41 …”
Section: Zincmentioning
confidence: 99%
“…Observational studies have consistently shown a protective association between vitamin D, 123 polyunsaturated fatty acids (PUFAs), especially n-6 PUFAs, 124 zinc gluconate, 125 and cancer incidence. As a consequence, the use of dietary supplements of these nutraceuticals for chemoprevention in patients with Barrett’s esophagus is being explored.…”
Section: Other Potential Chemopreventive Agentsmentioning
confidence: 99%
“…After controlling for multiple covariates, Barrett's patients who took 1 or more multivitamin pills a day had a significantly decreased risk of tetraploidy compared to those not taking multivitamins. Significant inverse associations were also observed between risk of EAC and supplemental vitamin C and vitamin E. 122 Observational studies have consistently shown a protective association between vitamin D, 123 polyunsaturated fatty acids (PUFAs), especially n-6 PUFAs, 124 zinc gluconate, 125 and cancer incidence. As a consequence, the use of dietary supplements of these nutraceuticals for chemoprevention in patients with Barrett's esophagus is being explored.…”
Section: Other Potential Chemopreventive Agentsmentioning
confidence: 99%